Retrospective of urolithiasis in dogs and cats at the Veterinary Hospital University Brazil – Fernandópolis/State of São Paulo between January 2018 and April 2019 (Research, Society and Development, 2022)
Urolithiasis is a disorder characterized by the presence of stones in the urinary tract, associated with multifactorial causes. It is frequent in small animals. The objective of the present study is to formulate a profile of the patients affected by this disease and contribute to more accurate diagnoses and more effective therapies, aiming to reduce reoccurrences so common to this disease. The study was carried out via the exploratory analysis of the medical records of patients diagnosed with urolithiasis at the Veterinary Hospital of Universidade Brasil – Fernandópolis Campus, State of São Paulo, between January 2018 and April 2019. Information regarding epidemiology, clinical signs, tests, diagnoses, instituted treatments, and reoccurrences was compiled. Subsequently, the data were analyzed, prevalence was determined, and graphs were elaborated using the Microsoft Office Excel® program. The results revealed a total of 20 animals diagnosed with urolithiasis during the study period, 16 (80%) of which were dogs and four (20%) were cats. It was observed that small dogs, mainly of the Shih-tzu breed, were the most affected, and aspects related to the environment such as home-only experience, sedentary lifestyle and contactants were recurrent. Therefore, for any animal that fits the profile and with consistent symptomatology, urolithiasis should be considered a differential diagnosis.